Life lessons with Uramichi Oniisan. 2 - Kuze, Gaku (Kodansha Comics, 2020)
"How did the cynical Uramichi end up hosting a TV show for small children? And how long is the studio going to let him keep teaching the kids the sorrow and exhaustion of life instead of, say, the ABCs? This dark comedy manga started as a webcomic and became a bestseller across Japan -- with an anime coming soon! While grappling with unexpected overtime, unreasonable working conditions, and unflattering costumes, Uramichi makes the acquaintance of other jaded professionals deep behind the scenes. Digital strategist Saito and merchandising whiz Hanbei almost seem like his kindred spirits, but their respective bad attitude and even worse temper keep the doors to Uramichi's fragile heart firmly shut. There must be someone out there who understands...right?"--